Evaluation of hemodialysis vascular access. Perspective from Mexico - García-Yañez, Juan C.; Serrano-Gavuzzo, Carlos A.; Arvizu-Hernandez, Mauricio; Moguel-González, Bernardo; Bravo, Erick (Frontiers in Nephrology, 2023)
Chronic kidney disease (CKD) has become a global health problem. In 2019 it was related to general global mortality of 2.53% (2.35-2.66%); in the same year, in Latin America, mortality related to CKD reached 5.25% (4.92-5.49%), with an annual increase of 3.37%; proving increased mortality of 102% between 1990 and 2017. A nephrology specialty in Mexico is established in his first 50 years. Still, younger nephrologists are interested in "new" sub-specialties of nephrology and learning novel techniques and problem-solved skills. Our group is the first in our country to focus solely and exclusively on comprehensive VA care and wants to position itself as the first Mexican interdisciplinary group of Vascular Access (GIMEXAV).